Pemanfaatan Teknologi Ozon Sebagai Green Technology pada Penanganan Hasil Pertanian - Budi Hartoyo; Yasmin Aulia Rachma (Universitas 17 Agustus 1945 Semarang, 2022)
Food and agricultural products are perishable, so they have the potential to experience losses, both in quality and quantity during the post-harvest process and processing due to physiological changes in the form of physical, chemical and microbiological. As an effort to reduce losses during post-harvest and physiological changes, it is necessary to apply appropriate technology (appropriate technology). The application of ozone technology in the handling of fruits, vegetables and fishery products has good prospects because it is felt to be safe and effective. Ozone (O3) has the main function, namely as an oxidizer and disinfectant or a combination of these two functions. The high oxidation potential of ozone can be used to kill bacteria (sterilization process), remove color (decolorization process), remove odors (deodorization process), and decompose organic compounds (degradation process). The treatment of ozonized water in the storage of food products and agricultural products does not damage their nutritional content, because the ozone content itself will be lost by evaporation. If ozone is exposed to sunlight it will break down into oxygen compounds again. Utilization of ozone technology is widely used to reduce contamination and extend the shelf life of fresh fruit, vegetables and fishery products. This paper examines and synthesizes several research results related to the use of ozone for fruits, vegetables and other agricultural commodities during the postharvest process and handling of agricultural products.